2013
DOI: 10.1016/j.compag.2013.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of feeding behavior of group housed growing–finishing pigs

Abstract: Feeding behavior and time spent eating contains valuable information that can be used for managing livestock, identifying sick animals, and determining genetic differences within a herd. Individual animal feeding behavior, in a commercial-sized pen, was recorded using radio-frequency identification (RFID) technology and a series of multiplexers. Data were collected on 960 pigs (mixed barrows, 406 and gilts, 600) over 4 grow-out periods. The animals entered the facility at 24.6 ± 5.4 kg (mean ± standard deviati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
44
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 23 publications
4
44
0
5
Order By: Relevance
“…High variability in the feeding patterns of individual, healthy pigs was found (Table 1) and is in agreement with the observations of other researchers (Brown-Brandl et al, 2013;Hessel and Van den Weghe, 2011).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…High variability in the feeding patterns of individual, healthy pigs was found (Table 1) and is in agreement with the observations of other researchers (Brown-Brandl et al, 2013;Hessel and Van den Weghe, 2011).…”
Section: Discussionsupporting
confidence: 92%
“…They also reported that in 64 % of the cases, the piglets were identified with a slight time delay between RFID and video. Brown-Brandl et al (2013) developed and validated an LF RFID system for monitoring feeding behaviour of cattle and swine and mention that the cattle system was in agreement with the video 98.3 % of the time, and the swine system was in agreement 98.7 % of the time. This agreement corresponds to the percentage of 20 s (swine system) or 30 s (cattle system) intervals where video and RFID system were identical (either both feeding or both not feeding).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They contain important information that can enable producers to better manage livestock (Brown-Brandl et al, 2013). For instance, research has shown that changes in feeding behavior can occur in response to thermal conditions of growing-finishing swine (Nienaber and Hahn, 2000), health status of sow and feedlot cattle (Cornou et al, 2008;Griffin, 2001), and diet of dairy goats (Adijaoude et al, 2000).…”
Section: Introductionmentioning
confidence: 99%